Typical continuous annealing technology of cold-rolled 700 MPa ultra-high strength low-alloy steel - MI Zhen-li; PAN Dian-jun; JIANG Hai-tao (工程科学学报)
In order to develop a new generation cold-rolled ultra-high strength low-alloy steel, continuous annealing experiments of a Ti-0.12%, Nb-0.076% cold-rolled ultra-high strength low-alloy steel were done on a continuous annealing test machine. The influence of annealing temperature on the phase composition, grain size, and mechanical properties of the steel was investigated at four dif-ferent annealing temperature ranges from 760℃ to 830℃. The final composition is ferrite and a small amount of bainite under 800℃ annealing and 400℃ over-aging conditions, the ferrite grain size is about 1.4 μn, and the yield strength reaches up to 700 MPa. A large number of nanometer size sub-crystal structures, a small number of dislocations, and nano-Ti and Nb precipitates are observed by scanning electron microscopy and transmission electron microscopy. Those microstructures improve the strength a lot.